2011
DOI: 10.1007/s10067-011-1870-7
|View full text |Cite|
|
Sign up to set email alerts
|

Health-related quality of life in women with fibromyalgia: clinical and psychological factors associated

Abstract: The objective of the study was to analyse the impact of fibromyalgia (FM) on health-related quality of life (HRQOL) and to identify clinical and psychological factors associated with the disease. A cross-sectional study was conducted with adult Portuguese women with FM. Analysed data were demographic, clinical and psychological variables and HRQOL: SF-36 and Fibromyalgia Impact Questionnaire (FIQ). The relationship between HRQOL and the other variables was made with a bivariate analysis. To assess the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 28 publications
1
45
1
3
Order By: Relevance
“…Using the FIQ and SF-36 forms, Türkyilmaz et al evaluated quality of life in FMS patients and determined a significant difference compared to a control group [58]. Various studies have shown that quality of life was negatively affected in FMS patients [13,14]. Different studies have shown that the quality of life was extremely low compared to control groups in FMS patients with diseases such as rheumatoid arthritis, osteoarthritis, chronic obstructive pulmonary disease and insulin-related diabetes [51].…”
Section: Fibromyalgia and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Using the FIQ and SF-36 forms, Türkyilmaz et al evaluated quality of life in FMS patients and determined a significant difference compared to a control group [58]. Various studies have shown that quality of life was negatively affected in FMS patients [13,14]. Different studies have shown that the quality of life was extremely low compared to control groups in FMS patients with diseases such as rheumatoid arthritis, osteoarthritis, chronic obstructive pulmonary disease and insulin-related diabetes [51].…”
Section: Fibromyalgia and Quality Of Lifementioning
confidence: 99%
“…The perception and evaluation of the quality of life of individuals is formed from life events in the context of cultural structure and value systems [12]. Several previous studies have shown the quality of life of FMS patients to be negatively affected [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] It is the second most common rheumatologic disease, with a worldwide prevalence of 0.5% to 5%. Women aged between 40 and 55 years are predominantly affected, with a prevalence approximately seven fold higher than in men.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de que existe un elevado número de investigaciones en CVRS de personas con fibromialgia, los estudios disponibles son diversos en relación con su tipología, es decir, algunos son de validación de las escalas genérica y específica, otros evalúan la CVRS como un desenlace secundario en ensayos clínicos 9 , y entre las investigaciones que analizan el perfil de la CVRS como desenlace primario, se presentan resultados divergentes en cuanto al grado de afectación o impacto de la enfermedad en las dimensiones del MOSSF-36 y del FIQ y discrepancias en cuanto a las dimensiones más afectadas 13,14 . Además, los estudios individuales presentan algunas limitaciones, que deben superarse, como las relacionadas con la validez externa de las conclusiones por presentar bajo tamaño de muestra o potencia estadística, no dar cuenta de diferencias relacionadas con el lugar de estudio o no presentar comparaciones entre los resultados del MOSSF-36 y del FIQ.…”
Section: Introductionunclassified